Low-environmental-pollution environment-friendly hot-melt coating filler as well as preparation method and application thereof

By chemically bonding modified inorganic fiber materials with hot-melt resin and wetting effect of low-melting-point glass powder in the Bi2O3-B2O3-SiO2 ternary system, the interfacial shear strength and compressive strength of hot-melt coatings are enhanced, solving the problems of single function and environmental pollution of inorganic fillers, and realizing hot-melt coating fillers with low environmental pollution and high mechanical properties.

CN120944395APending Publication Date: 2025-11-14ZHEJIANG TIANCHENG TRANSPORTATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511184800.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

The inorganic fillers commonly used in existing hot melt coatings have limited functions, and the mining of minerals such as quartz sand causes environmental pollution and fails to effectively improve the mechanical properties of the coating.

Method used

Using modified inorganic fiber materials, calcium silicate, calcium carbonate, and metakaolin, hot-melt coating fillers are prepared through surface treatment and composite microparticles. By utilizing the chemical bonding between the modified fiber materials and the hot-melt resin, combined with the wetting and viscosity changes of Sn-Bi binary alloy powder and Bi2O3-B2O3-SiO2 ternary system low-melting-point glass powder, the interfacial shear strength and compressive strength are enhanced.

Benefits of technology

It improves the mechanical properties of hot melt coatings, reduces environmental pollution, and has low energy consumption in the preparation process, without using highly toxic chemical reagents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of hot-melt coatings, in particular to a low-environmental-pollution environment-friendly hot-melt coating filler as well as a preparation method and application thereof. The hot-melt coating filler comprises the following components in parts by weight: 5-15 parts of a modified inorganic fiber material, 30-50 parts of first particles, 1-4 parts of Sn-Bi binary alloy powder, 10-25 parts of calcium silicate, 5-20 parts of calcium carbonate and 10-25 parts of metakaolin, the first particles are obtained by compounding ceramic microspheres and ternary system low-melting-point glass powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of hot melt coating technology, and in particular to a low-pollution, environmentally friendly hot melt coating filler, its preparation method and application. Background Technology

[0002] The inorganic fillers commonly used in existing hot melt coatings are mainly natural minerals or artificially calcined products such as quartz sand, heavy calcium carbonate, and kaolin. They have the following disadvantages: their function is singular, only serving as a skeleton or adding weight, without contributing to the mechanical properties of the coating; furthermore, for the core component of inorganic fillers in existing hot melt coatings, quartz sand, the reserves of high-quality quartz sand are limited, and the mining process causes damage to mountains and dust pollution.

[0003] Therefore, there is an urgent need for a new type of hot melt coating filler that not only meets the requirements of low environmental pollution during preparation and application, but also enhances the mechanical properties of hot melt coatings. Summary of the Invention

[0004] This disclosure provides a low-pollution, environmentally friendly hot-melt coating filler, its preparation method, and its application, in order to address the shortcomings of related technologies.

[0005] According to a first aspect of the present disclosure, a low-pollution, environmentally friendly hot-melt coating filler is provided, the hot-melt coating filler comprising the following components in parts by weight: 5-15 parts by weight of modified inorganic fiber material, 10-25 parts by weight of calcium silicate, 5-20 parts by weight of calcium carbonate, and 10-25 parts by weight of metakaolin; wherein the modified fiber material is obtained by surface treatment of inorganic fiber material with a first mixed solution, the first mixed solution comprising at least one alkali and at least one alcohol or ether; the inorganic fiber material is selected from at least one of glass fiber, alumina fiber, zirconium oxide fiber, aluminum silicate fiber, basalt fiber, andesite fiber, titanate fiber, boron aluminosilicate fiber, carbon fiber, graphite fiber, silicon carbide fiber, silicon nitride fiber, boron nitride fiber, boron fiber, boron carbon nitride fiber, sepiolite fiber, and palygorskite fiber.

[0006] In one aspect of the embodiments of this disclosure, the hot melt coating filler can be used in systems of hot melt road marking paint, polyester resin hot melt paint, epoxy resin hot melt paint, and polyurethane hot melt paint.

[0007] In one aspect of this disclosure, the hot melt coating filler can be used in conjunction with C5 petroleum resin or C5 / C9 copolymer petroleum resin.

[0008] In one aspect of the embodiments of this disclosure, preferably, the inorganic fiber material is selected from at least one of alumina fiber, zirconium oxide fiber, aluminum silicate fiber, basalt fiber, andesite fiber, titanate fiber, boroaluminosilicate fiber, sepiolite fiber, and palygorskite fiber.

[0009] In one aspect of this disclosure, in the first mixed solution, the alkali is selected from sodium hydroxide; the alcohol is selected from any one of ethylene glycol, 1,2-propanediol, and diethylene glycol; the first mixed solution further includes sodium dodecyl sulfate or hexadecyltrimethylammonium bromide; the inorganic fiber material is selected from any one of the following: basalt fiber, andesite fiber, a combination of alumina fiber and aluminosilicate fiber, a combination of basalt fiber and aluminosilicate fiber, a combination of basalt fiber and alumina fiber, a combination of andesite fiber and aluminosilicate fiber, and a combination of andesite fiber and alumina fiber.

[0010] In one aspect of the embodiments of this disclosure, preferably, in the first mixed solution, the base is selected from sodium hydroxide; the alcohol is selected from 1,2-propanediol; and the first mixed solution further includes sodium dodecyl sulfate.

[0011] In one aspect of the embodiments of this disclosure, preferably, the inorganic fiber material is selected from basalt fiber or andesite fiber.

[0012] In one aspect of the present disclosure, the surface treatment includes the following steps: Step 1-a: the inorganic fiber material is washed with water, washed with alcohol, and then dried.

[0013] Step 2-a: Prepare the first mixed solution.

[0014] Step 3-a: Add the dried inorganic fiber material to the first mixed solution, heat to 70℃-85℃, and react for 3-8 hours.

[0015] Step 4-a: After the reaction is complete, the modified fiber material is obtained by washing with water and drying.

[0016] In one aspect of the embodiments of this disclosure, the hot melt coating filler further comprises 30-50 parts by weight of first microparticles and 1-4 parts by weight of Sn-Bi binary alloy powder; the first microparticles are obtained by combining ceramic microspheres and ternary low-melting-point glass powder.

[0017] In one aspect of this disclosure, the mass ratio of ceramic microspheres to ternary low-melting-point glass powder is selected from 1:(1-3).

[0018] In one aspect of this disclosure, the ceramic microspheres are selected from alumina microspheres, zirconia microspheres, cenospheres, silicon nitride microspheres, or silicon carbide microspheres; the ternary low-melting-point glass powder is selected from Bi2O3-B2O3-SiO2 ternary low-melting-point glass powder.

[0019] In one aspect of the present disclosure, the low melting point glass powder of the Bi2O3-B2O3-SiO2 ternary system is prepared by the following steps: Step 1-b: Bi2O3, B2O3, SiO2, Li2O, Na2O, K2O, KF, ZnO and Al2O3 are weighed and added to a ball mill jar, and the mixture is obtained after ball milling.

[0020] Step 2-b: Pour the mixture into a corundum crucible and place it in a muffle furnace for heating.

[0021] Step 3-b: Pour the melt into water and cool it rapidly to obtain granular glass. After drying, crushing, and grinding, the glass is passed through a 250-350 mesh sieve to obtain the low melting point glass powder of the Bi2O3-B2O3-SiO2 ternary system.

[0022] In one aspect of this disclosure, based on the total mass of the mixture, the mass percentage of Bi2O3 is selected from 50%-60%, the mass percentage of B2O3 is selected from 18%-22%, the mass percentage of SiO2 is selected from 10%-15%, the mass percentage of Li2O is selected from 2%-4%, the mass percentage of Na2O is selected from 2%-4%, the mass percentage of K2O is selected from 1.5%-2.5%, the mass percentage of KF is selected from 1.5%-2.5%, the mass percentage of ZnO is selected from 2%-4%, and the mass percentage of Al2O3 is selected from 1.5%-2.5%.

[0023] In one aspect of the present disclosure, the first microparticle is prepared by the following steps: Step 1-c: ceramic microspheres, low melting point glass powder of Bi2O3-B2O3-SiO2 ternary system and additives are put into a V-type mixer and mixed for 30-70 min to obtain the raw material of step 1-c.

[0024] Step 2-c: Add the raw material obtained in step 1-c to the mechanical blender and mix for 5-15 minutes to obtain the raw material of step 2-c.

[0025] Step 3-c: Add the raw material obtained in step 2-c into a tunnel furnace and heat it to melt at 600℃-700℃.

[0026] Step 4-c: Cool and classify the heated and melted product to obtain the first microparticle.

[0027] According to a second aspect of the present disclosure, a method for preparing the aforementioned hot melt coating filler is provided, the method comprising the following steps: Step 1: preparing first microparticles.

[0028] Step 2: Prepare modified fiber materials.

[0029] Step 3: After thoroughly mixing the first microparticle, Sn-Bi binary alloy powder, modified inorganic fiber material, calcium silicate, calcium carbonate and metakaolin, the hot melt coating filler is obtained.

[0030] According to a third aspect of the present disclosure, the application of the aforementioned hot melt coating filler in a hot melt coating composition is provided.

[0031] The technical solutions provided by the embodiments of this disclosure may include the following beneficial effects: (1) In the prior art, the construction temperature of a considerable number of hot melt coatings is between 180℃ and 220℃. This disclosure prepares the first microparticle of a Bi2O3-B2O3-SiO2 ternary system low melting point glass powder composite ceramic microsphere; wherein, the softening temperature of the Bi2O3-B2O3-SiO2 ternary system low melting point glass powder is also close to between 180℃ and 220℃. Therefore, when the hot melt coating is heated to about 180℃-220℃, Bi2O3-B2O3-SiO2... The viscosity of low-melting-point glass powder in the iO2 ternary system decreases significantly. Under capillary action, the molten glass spreads along the interface between the hot-melt resin and the filler, and undergoes chemical reactions with carboxyl / anhydride groups on the hot-melt resin, including -Si-OC- chemical bonding, forming "micro-weld points" that enhance wet adhesion retention, interfacial shear strength, and compressive strength. When cooled, the glass powder re-hardens, and the ceramic microspheres become "rigid anchors," dispersing the resin shrinkage stress and thus improving mechanical properties. In addition, the ceramic microspheres themselves are also attachment points for the glass powder, improving the dispersion of the glass powder and preventing agglomeration.

[0032] (2) The present disclosure also prepared a modified fiber material, the surface of which was modified to obtain abundant Si-OH and Al-OH, which can undergo rapid dehydration condensation with carboxyl / anhydride groups on hot melt resin at 180℃-220℃ to generate -Si-OC- chemical bonds, which also enhances the interfacial shear strength and compressive strength.

[0033] (3) This disclosure also provides Sn-Bi binary alloy powder as a lubricant / wetting agent with a melting point of about 140°C-155°C. When the hot melt coating is heated to about 180°C-220°C, the Sn-Bi binary alloy powder melts and the Sn-Bi liquid phase pre-wets the hot melt resin-filler interface, thereby allowing the molten glass to spread better along the hot melt resin-filler interface under capillary action.

[0034] (4) The modified fiber material and the first microparticle prepared in this disclosure are both low-environmental-pollution environmentally friendly materials. Their preparation process has low energy consumption and does not use highly toxic chemical reagents.

[0035] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Detailed Implementation

[0036] Exemplary embodiments will now be described in detail. The implementation methods described in the following exemplary embodiments do not represent all implementation methods consistent with this disclosure.

[0037] The terminology used in this disclosure is for the purpose of describing particular embodiments only and is not intended to be limiting of the disclosure. The singular forms “a,” “the,” and “the” as used in this disclosure and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any and all possible combinations of one or more of the associated listed items.

[0038] For the sake of brevity, this article only discloses a few specific numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.

[0039] In this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0040] In this description, unless otherwise stated, "above" and "below" include the stated number.

[0041] Unless otherwise stated, the terms used in this disclosure have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the values ​​of the parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this disclosure).

[0042] The term "about" is used to describe and indicate small variations. When used in conjunction with an event or situation, the term may refer to examples in which the event or situation occurred precisely or in examples in which the event or situation occurred very approximately. For example, when used in conjunction with numerical values, the term may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. Additionally, quantities, ratios, and other numerical values ​​are sometimes presented in range format herein. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only numerical values ​​explicitly specified as range limits but also all individual numerical values ​​or subranges covered within the range, as if each numerical value and subrange were explicitly specified.

[0043] The list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0044] The present invention will be further described below by way of specific embodiments. Unless otherwise specified, all chemical reagents used in the embodiments of the present invention were obtained through conventional commercial means. Unless otherwise specified, all contents mentioned below are mass contents. Unless otherwise specified, it is understood that the process was carried out at room temperature.

[0045] Example: Example 1: Example 1 includes the following steps: 1. Preparation of the first microparticle: Weigh 52 parts by weight of Bi2O3, 20 parts by weight of B2O3, 13 parts by weight of SiO2, 3 parts by weight of Li2O, 3 parts by weight of Na2O, 2 parts by weight of K2O, 2 parts by weight of KF, 3 parts by weight of ZnO and 2 parts by weight of Al2O3 and add them to a ball mill jar. Add Φ5mm zirconia balls, the ball-to-material ratio is 2:1, the ball mill speed is 180r / min, the ball milling time is 4h, and a mixture is obtained after ball milling.

[0046] The mixture was poured into an alumina crucible and placed in a muffle furnace for heating. The muffle furnace heating program was as follows: heating from room temperature to 600°C at a rate of 3°C / min. -1Hold at 600℃ for 30 minutes to remove decomposition gases; then continue heating to 1150℃ at a rate of 5℃ / min. -1 Then keep warm for 60 minutes.

[0047] The melt was poured into water and rapidly cooled to obtain granular glass. After drying, crushing, and grinding, it was passed through a 325-mesh sieve to obtain the low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system of Example 1.

[0048] Ceramic microspheres (alumina microspheres, D50 of approximately 15 μm), the previously prepared Bi2O3-B2O3-SiO2 ternary system low-melting-point glass powder, and additives (lithium carbonate, for crack prevention) were added to a V-type mixer and mixed for 60 min (cylinder rotation speed of 30 r / min, with an angle of 60° between the two cylinders) to obtain the first raw material; wherein, the mass ratio of alumina microspheres, Bi2O3-B2O3-SiO2 ternary system low-melting-point glass powder, and lithium carbonate was selected as 1:2:0.05.

[0049] The first batch of raw material was added to a mechanical fusion machine (rotation speed 2500 r / min, water cooling below 40℃) and mixed for 8 minutes to obtain the second batch of raw material. During this process, glass powder was sheared and embedded into the surface of the microspheres at high speed, forming a rough pre-coating.

[0050] The second batch of raw material is added to the mesh belt tunnel furnace and heated to 5°C for 1 minute. -1 The heating rate is increased from room temperature to 680℃, and the glass powder is heated and melted. The melting section is held for 3 minutes to allow the glass powder to completely melt and self-level, and the slow cooling section is held for 2 minutes to prevent the glass powder from cracking due to thermal shock.

[0051] The heated and melted product was naturally cooled in a nitrogen environment, and a vibrating screen was used to remove large adhering particles and dust; thus, the first microparticle of Example 1 was obtained.

[0052] 2. Preparation of modified fiber material: Basalt fibers were washed with water and alcohol, and then dried. A first mixed solution was prepared. In the first mixed solution, the volume percentage of 1,2-propanediol was 36%, the mass fraction of sodium hydroxide was 8%, and the mass fraction of sodium dodecyl sulfate was 0.05%. The dried basalt fibers were immersed in the first mixed solution, heated to 80°C, and reacted for 5 hours. After the reaction was completed, the fibers were washed with water and dried to obtain the modified fiber material of Example 1.

[0053] 3. Preparation of the filler of Example 1: 45 parts by weight of the first microparticle, 2 parts by weight of Sn-Bi binary alloy powder (the Sn-Bi binary alloy powder is obtained by cutting and crushing commercially available Sn-Bi binary alloy and passing it through a 40-mesh sieve), 10 parts by weight of modified inorganic fiber material, 12 parts by weight of calcium silicate, 8 parts by weight of calcium carbonate and 15 parts by weight of metakaolin are thoroughly mixed to obtain the hot melt coating filler of Example 1.

[0054] Example 2: Example 2 includes the following steps: 1. Preparation of the first microparticles: Weigh 52 parts by weight of Bi2O3, 20 parts by weight of B2O3, 13 parts by weight of SiO2, 3 parts by weight of Li2O, 3 parts by weight of Na2O, 2 parts by weight of K2O, 2 parts by weight of KF, 3 parts by weight of ZnO and 2 parts by weight of Al2O3 and add them to a ball mill jar. Add Φ5mm zirconia balls, the ball-to-material ratio is 2:1, the ball mill speed is 180r / min, the ball milling time is 4h, and a mixture is obtained after ball milling.

[0055] The mixture was poured into an alumina crucible and placed in a muffle furnace for heating. The muffle furnace heating program was as follows: heating from room temperature to 600°C at a rate of 3°C / min. -1 Hold at 600℃ for 30 minutes to remove decomposition gases; then continue heating to 1150℃ at a rate of 5℃ / min. -1 Then keep warm for 60 minutes.

[0056] The melt was poured into water and rapidly cooled to obtain granular glass. After drying, crushing, and grinding, it was passed through a 325-mesh sieve to obtain the low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system of Example 2.

[0057] Ceramic microspheres (alumina microspheres, D50 of approximately 15 μm), the previously prepared Bi2O3-B2O3-SiO2 ternary system low-melting-point glass powder, and additives (lithium carbonate, for crack prevention) were added to a V-type mixer and mixed for 60 min (cylinder rotation speed of 30 r / min, with an angle of 60° between the two cylinders) to obtain the first raw material; wherein, the mass ratio of alumina microspheres, Bi2O3-B2O3-SiO2 ternary system low-melting-point glass powder, and lithium carbonate was selected as 1:2:0.05.

[0058] The first batch of raw material was added to a mechanical fusion machine (rotation speed 2500 r / min, water cooling below 40℃) and mixed for 8 minutes to obtain the second batch of raw material. During this process, glass powder was sheared and embedded into the surface of the microspheres at high speed, forming a rough pre-coating.

[0059] The second batch of raw material is added to the mesh belt tunnel furnace and heated to 5°C for 1 minute. -1The heating rate is increased from room temperature to 680℃, and the glass powder is heated and melted. The melting section is held for 3 minutes to allow the glass powder to completely melt and self-level, and the slow cooling section is held for 2 minutes to prevent the glass powder from cracking due to thermal shock.

[0060] The heated and melted product was naturally cooled in a nitrogen environment, and a vibrating screen was used to remove large adhering particles and dust; thus, the first microparticle of Example 2 was obtained.

[0061] 2. Preparation of modified fiber material: Basalt fibers were washed with water and alcohol, and then dried. A first mixed solution was prepared. In the first mixed solution, the volume percentage of 1,2-propanediol was 36%, the mass fraction of sodium hydroxide was 8%, and the mass fraction of sodium dodecyl sulfate was 0.05%. The dried basalt fibers were immersed in the first mixed solution, heated to 80°C, and reacted for 5 hours. After the reaction was completed, the fibers were washed with water and dried to obtain the modified fiber material of Example 2.

[0062] 3. Preparation of the filler of Example 2: 45 parts by weight of the first microparticle, 10 parts by weight of the modified inorganic fiber material, 13 parts by weight of calcium silicate, 9 parts by weight of calcium carbonate and 15 parts by weight of metakaolin were thoroughly mixed to obtain the hot melt coating filler of Example 2.

[0063] The difference between Example 2 and Example 1 is that Example 2 does not contain Sn-Bi binary alloy powder.

[0064] Example 3: Example 3 includes the following steps: 1. Preparation of the first microparticles: Weigh 52 parts by weight of Bi2O3, 20 parts by weight of B2O3, 13 parts by weight of SiO2, 3 parts by weight of Li2O, 3 parts by weight of Na2O, 2 parts by weight of K2O, 2 parts by weight of KF, 3 parts by weight of ZnO and 2 parts by weight of Al2O3 and add them to a ball mill jar. Add Φ5mm zirconia balls, the ball-to-material ratio is 2:1, the ball mill speed is 180r / min, the ball milling time is 4h, and a mixture is obtained after ball milling.

[0065] The mixture was poured into an alumina crucible and placed in a muffle furnace for heating. The muffle furnace heating program was as follows: heating from room temperature to 600°C at a rate of 3°C / min. -1 Hold at 600℃ for 30 minutes to remove decomposition gases; then continue heating to 1150℃ at a rate of 5℃ / min. -1 Then keep warm for 60 minutes.

[0066] The melt was poured into water and rapidly cooled to obtain granular glass. After drying, crushing, and grinding, it was passed through a 325-mesh sieve to obtain the low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system of Example 3.

[0067] The prepared low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system was directly used as the first particle.

[0068] 2. Preparation of modified fiber material: Basalt fibers were washed with water and alcohol, and then dried. A first mixed solution was prepared. In the first mixed solution, the volume percentage of 1,2-propanediol was 36%, the mass fraction of sodium hydroxide was 8%, and the mass fraction of sodium dodecyl sulfate was 0.05%. The dried basalt fibers were immersed in the first mixed solution, heated to 80°C, and reacted for 5 hours. After the reaction was completed, the fibers were washed with water and dried to obtain the modified fiber material of Example 3.

[0069] 3. Preparation of the filler in Example 3: 45 parts by weight of the first microparticle, 2 parts by weight of Sn-Bi binary alloy powder (the Sn-Bi binary alloy powder is obtained by cutting and crushing commercially available Sn-Bi binary alloy and passing it through a 40-mesh sieve), 10 parts by weight of modified inorganic fiber material, 12 parts by weight of calcium silicate, 8 parts by weight of calcium carbonate and 15 parts by weight of metakaolin are thoroughly mixed to obtain the hot melt coating filler of Example 3.

[0070] The main difference between Example 3 and Example 1 is that in Example 3, the low-melting-point glass powder of the prepared Bi2O3-B2O3-SiO2 ternary system is directly used as the first particle.

[0071] Example 4: Example 4 includes the following steps: 1. Preparation of the first microparticles: Weigh 52 parts by weight of Bi2O3, 20 parts by weight of B2O3, 13 parts by weight of SiO2, 3 parts by weight of Li2O, 3 parts by weight of Na2O, 2 parts by weight of K2O, 3 parts by weight of ZnO and 2 parts by weight of Al2O3 and add them to a ball mill jar. Add Φ5mm zirconia balls, the ball-to-material ratio is 2:1, the ball mill speed is 180r / min, the ball milling time is 4h, and a mixture is obtained after ball milling.

[0072] The mixture was poured into an alumina crucible and placed in a muffle furnace for heating. The muffle furnace heating program was as follows: heating from room temperature to 600°C at a rate of 3°C / min. -1 Hold at 600℃ for 30 minutes to remove decomposition gases; then continue heating to 1150℃ at a rate of 5℃ / min. -1 Then keep warm for 60 minutes.

[0073] The melt was poured into water and rapidly cooled to obtain granular glass. After drying, crushing, and grinding, it was passed through a 325-mesh sieve to obtain the low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system of Example 4.

[0074] Ceramic microspheres (alumina microspheres, D50 of approximately 15 μm), the previously prepared Bi2O3-B2O3-SiO2 ternary system low-melting-point glass powder, and additives (lithium carbonate, for crack prevention) were added to a V-type mixer and mixed for 60 min (cylinder rotation speed of 30 r / min, with an angle of 60° between the two cylinders) to obtain the first raw material; wherein, the mass ratio of alumina microspheres, Bi2O3-B2O3-SiO2 ternary system low-melting-point glass powder, and lithium carbonate was selected as 1:2:0.05.

[0075] The first batch of raw material was added to a mechanical fusion machine (rotation speed 2500 r / min, water cooling below 40℃) and mixed for 8 minutes to obtain the second batch of raw material. During this process, glass powder was sheared and embedded into the surface of the microspheres at high speed, forming a rough pre-coating.

[0076] The second batch of raw material is added to the mesh belt tunnel furnace and heated to 5°C for 1 minute. -1 The heating rate is increased from room temperature to 680℃, and the glass powder is heated and melted. The melting section is held for 3 minutes to allow the glass powder to completely melt and self-level, and the slow cooling section is held for 2 minutes to prevent the glass powder from cracking due to thermal shock.

[0077] The heated and melted product was naturally cooled in a nitrogen environment, and a vibrating screen was used to remove large adhering particles and dust; thus, the first microparticle of Example 4 was obtained.

[0078] 2. Preparation of modified fiber material: Basalt fibers were washed with water and alcohol, and then dried. A first mixed solution was prepared. In the first mixed solution, the volume percentage of 1,2-propanediol was 36%, the mass fraction of sodium hydroxide was 8%, and the mass fraction of sodium dodecyl sulfate was 0.05%. The dried basalt fibers were immersed in the first mixed solution, heated to 80°C, and reacted for 5 hours. After the reaction was completed, the fibers were washed with water and dried to obtain the modified fiber material of Example 4.

[0079] 3. Preparation of the filler of Example 4: 45 parts by weight of the first microparticle, 2 parts by weight of Sn-Bi binary alloy powder (the Sn-Bi binary alloy powder is obtained by cutting and crushing commercially available Sn-Bi binary alloy and passing it through a 40-mesh sieve), 10 parts by weight of modified inorganic fiber material, 12 parts by weight of calcium silicate, 8 parts by weight of calcium carbonate and 15 parts by weight of metakaolin are thoroughly mixed to obtain the hot melt coating filler of Example 4.

[0080] The main difference between Example 4 and Example 1 is that KF was not added in Example 4 when preparing the low melting point glass powder of the Bi2O3-B2O3-SiO2 ternary system.

[0081] Example 5: Example 5 includes the following steps: 1. Preparation of modified fiber material: Basalt fiber is washed with water and alcohol and then dried; a first mixed solution is prepared; in the first mixed solution, the volume percentage of 1,2-propanediol is 36%, the mass fraction of sodium hydroxide is 8%, and the mass fraction of sodium dodecyl sulfate is 0.05%. The dried basalt fiber is immersed in the first mixed solution, heated to 80°C, and reacted for 5 hours; after the reaction is completed, it is washed with water and dried to obtain the modified fiber material of Example 5.

[0082] 2. Preparation of the filler in Example 5: 45 parts by weight of the first microparticles (alumina microspheres, D50 of about 15 μm), 2 parts by weight of Sn-Bi binary alloy powder (the Sn-Bi binary alloy powder was obtained by cutting and crushing commercially available Sn-Bi binary alloy and passing it through a 40-mesh sieve), 10 parts by weight of modified inorganic fiber material, 12 parts by weight of calcium silicate, 8 parts by weight of calcium carbonate and 15 parts by weight of metakaolin were thoroughly mixed to obtain the hot melt coating filler of Example 5.

[0083] The main difference between Example 5 and Example 1 is that in Example 3, alumina microspheres were used directly as the first microparticle.

[0084] Example 6: Example 6 includes the following steps: 1. Preparation of ternary low melting point glass powder: Weigh 52 parts by weight of Bi2O3, 20 parts by weight of B2O3, 13 parts by weight of SiO2, 3 parts by weight of Li2O, 3 parts by weight of Na2O, 2 parts by weight of K2O, 2 parts by weight of KF, 3 parts by weight of ZnO and 2 parts by weight of Al2O3 and add them to a ball mill jar. Add Φ5mm zirconia balls, the ball-to-material ratio is 2:1, the ball mill speed is 180r / min, the ball milling time is 4h, and a mixture is obtained after ball milling.

[0085] The mixture was poured into an alumina crucible and placed in a muffle furnace for heating. The muffle furnace heating program was as follows: heating from room temperature to 600°C at a rate of 3°C / min. -1 Hold at 600℃ for 30 minutes to remove decomposition gases; then continue heating to 1150℃ at a rate of 5℃ / min. -1 Then keep warm for 60 minutes.

[0086] The melt was poured into water and rapidly cooled to obtain granular glass. After drying, crushing, and grinding, it was passed through a 325-mesh sieve to obtain the low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system in Example 6.

[0087] 2. Preparation of modified fiber material: Basalt fibers were washed with water and alcohol, and then dried. A first mixed solution was prepared. In the first mixed solution, the volume percentage of 1,2-propanediol was 36%, the mass fraction of sodium hydroxide was 8%, and the mass fraction of sodium dodecyl sulfate was 0.05%. The dried basalt fibers were immersed in the first mixed solution, heated to 80°C, and reacted for 5 hours. After the reaction was completed, the fibers were washed with water and dried to obtain the modified fiber material of Example 6.

[0088] 3. Preparation of the filler in Example 6: 30 parts by weight of ternary low-melting-point glass powder, 15 parts by weight of alumina microspheres, 2 parts by weight of Sn-Bi binary alloy powder (the Sn-Bi binary alloy powder is obtained by cutting and crushing commercially available Sn-Bi binary alloy and passing it through a 40-mesh sieve), 10 parts by weight of modified inorganic fiber material, 12 parts by weight of calcium silicate, 8 parts by weight of calcium carbonate and 15 parts by weight of metakaolin are thoroughly mixed to obtain the hot-melt coating filler of Example 6.

[0089] The main difference between Example 6 and Example 1 is that in Example 6, alumina microspheres and ternary low-melting-point glass powder were not combined, but added separately.

[0090] Example 7: Example 7 includes the following steps: 1. Preparation of the first microparticle: ceramic microspheres (alumina microspheres, D50 of about 15 μm), commercially available ordinary ultrafine glass powder (mainly composed of high-purity silicon dioxide and alumina, D50=45 μm, its particle size is close to that of the ternary system low melting point glass powder prepared above) and additives (lithium carbonate, used for crack prevention) are put into a V-type mixer and mixed for 60 min (the cylinder speed is 30 r / min, and the angle between the two cylinders is 60°) to obtain the first raw material; wherein, the mass ratio of alumina microspheres, ordinary ultrafine glass powder and lithium carbonate is selected from 1:2:0.05.

[0091] The first batch of raw material was added to a mechanical fusion machine (rotation speed 2500 r / min, water cooling below 40℃) and mixed for 8 minutes to obtain the second batch of raw material. During this process, glass powder was sheared and embedded into the surface of the microspheres at high speed, forming a rough pre-coating.

[0092] The second batch of raw material is added to the mesh belt tunnel furnace and heated to 5°C for 1 minute. -1 The heating rate is increased from room temperature to 680℃, and the glass powder is heated and melted. The melting section is held for 3 minutes to allow the glass powder to completely melt and self-level, and the slow cooling section is held for 2 minutes to prevent the glass powder from cracking due to thermal shock.

[0093] The heated and melted product was naturally cooled in a nitrogen environment, and a vibrating screen was used to remove large adhering particles and dust; thus, the first microparticle of Example 7 was obtained.

[0094] 2. Preparation of modified fiber material: Basalt fibers were washed with water and alcohol, and then dried. A first mixed solution was prepared. In the first mixed solution, the volume percentage of 1,2-propanediol was 36%, the mass fraction of sodium hydroxide was 8%, and the mass fraction of sodium dodecyl sulfate was 0.05%. The dried basalt fibers were immersed in the first mixed solution, heated to 80°C, and reacted for 5 hours. After the reaction was completed, the fibers were washed with water and dried to obtain the modified fiber material of Example 7.

[0095] 3. Preparation of the filler of Example 7: 45 parts by weight of the first microparticle, 2 parts by weight of Sn-Bi binary alloy powder (the Sn-Bi binary alloy powder is obtained by cutting and crushing commercially available Sn-Bi binary alloy and passing it through a 40-mesh sieve), 10 parts by weight of modified inorganic fiber material, 12 parts by weight of calcium silicate, 8 parts by weight of calcium carbonate and 15 parts by weight of metakaolin are thoroughly mixed to obtain the hot melt coating filler of Example 7.

[0096] The main difference between Example 7 and Example 1 is that Example 7 did not prepare low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system, but instead used ordinary ultrafine glass powder.

[0097] Performance testing: 30 parts by weight of samples from Examples 1-7 were weighed and mixed with 100 parts by weight of C5 petroleum resin, 6 parts by weight of epoxidized soybean oil, and 3 parts by weight of PE wax, respectively. The mixture was heated to 220°C until it was completely melted, stirred thoroughly for 10 minutes, cooled at room temperature for 5 minutes, and then pulverized to obtain hot-melt coating samples. The leveling properties and compressive strength were tested according to the method in JT / T280-2004, and the results are shown in Table 1. Table 1:

[0098] As can be seen, compared with Example 2, Example 1 has certain advantages in terms of leveling and compressive strength. This is because Sn-Bi binary alloy powder, as a lubricant / wetting agent, has a melting point of about 140°C-155°C. When the hot melt coating is heated to about 180°C-220°C, the Sn-Bi binary alloy powder melts, and the Sn-Bi liquid phase pre-wets the hot melt resin-filler interface, thereby allowing the molten glass to spread better along the hot melt resin-filler interface under capillary action, thus enhancing its performance in terms of leveling and compressive strength.

[0099] Compared to Example 3, Example 1 has a significant advantage in terms of leveling properties. This is because the ceramic microspheres themselves are also the attachment points for the glass powder, which can improve the dispersion of the glass powder and prevent agglomeration.

[0100] Compared to Example 4, Example 1 has certain advantages in terms of leveling and compressive strength. This is because KF can significantly reduce the softening point of the low-melting-point glass powder in the Bi2O3-B2O3-SiO2 ternary system, bringing it down to the hot-melt coating temperature range of C5 petroleum resin. This facilitates the spread of molten glass along the hot-melt resin-filler interface under capillary action.

[0101] Compared to Example 5, Example 1 has significant advantages in terms of leveling and compressive strength. This is because the low melting point of the Bi2O3-B2O3-SiO2 ternary system glass powder lowers its softening point to within the hot-melt coating temperature range of C5 petroleum resin. Under capillary action, the molten glass spreads along the interface between the hot-melt resin and the filler, and undergoes chemical reactions with carboxyl / anhydride groups on the hot-melt resin, including -Si-OC- chemical bonding, to form "micro-weld points," which enhances wet adhesion retention, interfacial shear strength, and compressive strength. When cooled, the glass powder hardens again, and the ceramic microspheres become "rigid anchors," dispersing the resin shrinkage stress, thereby improving mechanical properties.

[0102] Compared to Example 6, Example 1 has certain advantages in terms of leveling and compressive strength. This is because the composite ceramic microspheres can better serve as attachment points for glass powder, improve the dispersion of glass powder, avoid agglomeration, and enhance mechanical properties.

[0103] Compared to Example 7, Example 1 has certain advantages in terms of leveling and compressive strength. This is because the softening point of the Bi2O3-B2O3-SiO2 ternary system low melting point glass powder prepared in this disclosure is significantly lower than that of commercially available ordinary glass powder, so it can spread along the hot melt resin-filler interface under capillary action.

[0104] Other embodiments of this disclosure will readily occur to those skilled in the art upon consideration of the specification and practice of the disclosure herein. This disclosure is intended to cover any variations, uses, or adaptations of this disclosure that follow the general principles of this disclosure and include common knowledge or customary techniques in the art not disclosed herein.

Claims

1. A low-pollution, environmentally friendly hot-melt coating filler, characterized in that, The hot-melt coating filler comprises the following components in parts by weight: 5-15 parts by weight of modified inorganic fiber material, 10-25 parts by weight of calcium silicate, 5-20 parts by weight of calcium carbonate, and 10-25 parts by weight of metakaolin; wherein the modified fiber material is obtained by surface treatment of inorganic fiber material with a first mixed solution, the first mixed solution comprising at least one alkali and at least one alcohol or ether; the inorganic fiber material is selected from at least one of glass fiber, alumina fiber, zirconium oxide fiber, aluminum silicate fiber, basalt fiber, andesite fiber, titanate fiber, boron aluminum silicate fiber, carbon fiber, graphite fiber, silicon carbide fiber, silicon nitride fiber, boron nitride fiber, boron fiber, boron carbon nitride fiber, sepiolite fiber, and palygorskite fiber.

2. The hot-melt coating filler according to claim 1, characterized in that, In the first mixed solution, the alkali is selected from sodium hydroxide; the alcohol is selected from any one of ethylene glycol, 1,2-propanediol, and diethylene glycol; the first mixed solution also includes sodium dodecyl sulfate or hexadecyltrimethylammonium bromide; the inorganic fiber material is selected from any one of the following: basalt fiber, andesite fiber, a combination of alumina fiber and aluminosilicate fiber, a combination of basalt fiber and aluminosilicate fiber, a combination of basalt fiber and alumina fiber, a combination of andesite fiber and aluminosilicate fiber, and a combination of andesite fiber and alumina fiber.

3. The hot-melt coating filler according to claim 1 or 2, characterized in that, The surface treatment includes the following steps: Step 1-a: The inorganic fiber material is washed with water and alcohol and then dried; Step 2-a: The first mixed solution is prepared; Step 3-a: The dried inorganic fiber material is added to the first mixed solution, the temperature is raised to 70℃-85℃, and the reaction is carried out for 3-8 hours; Step 4-a: After the reaction is completed, the modified fiber material is obtained after washing with water and drying.

4. The hot-melt coating filler according to claim 1, characterized in that, The hot-melt coating filler also contains 30-50 parts by weight of first microparticles and 1-4 parts by weight of Sn-Bi binary alloy powder; the first microparticles are obtained by combining ceramic microspheres and ternary low-melting-point glass powder.

5. The hot-melt coating filler according to claim 4, characterized in that, The ceramic microspheres are selected from alumina microspheres, zirconia microspheres, cenospheres, silicon nitride microspheres, or silicon carbide microspheres; the ternary low-melting-point glass powder is selected from Bi2O3-B2O3-SiO2 ternary low-melting-point glass powder.

6. The hot-melt coating filler according to claim 5, characterized in that, The low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system is prepared by the following steps: Step 1-b: Weigh Bi2O3, B2O3, SiO2, Li2O, Na2O, K2O, KF, ZnO and Al2O3 and add them to a ball mill jar. After ball milling, a mixture is obtained; Step 2-b: Pour the mixture into a corundum crucible and heat it in a muffle furnace; Step 3-b: Pour the melt into water and cool it rapidly to obtain granular glass. After drying, crushing and grinding, the granules are passed through a 250-350 mesh sieve to obtain the low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system.

7. The hot-melt coating filler according to claim 6, characterized in that, Based on the total mass of the mixture, the mass percentage of Bi2O3 is selected from 50%-60%, the mass percentage of B2O3 is selected from 18%-22%, the mass percentage of SiO2 is selected from 10%-15%, the mass percentage of Li2O is selected from 2%-4%, the mass percentage of Na2O is selected from 2%-4%, the mass percentage of K2O is selected from 1.5%-2.5%, the mass percentage of KF is selected from 1.5%-2.5%, the mass percentage of ZnO is selected from 2%-4%, and the mass percentage of Al2O3 is selected from 1.5%-2.5%.

8. The hot-melt coating filler according to any one of claims 4-7, characterized in that, The first microparticle is prepared through the following steps: Step 1-c: Ceramic microspheres, low-melting-point glass powder of the Bi2O3-B2O3-SiO2 ternary system and additives are added to a V-type mixer and mixed for 30-70 min to obtain the raw material of Step 1-c; Step 2-c: The raw material obtained in Step 1-c is added to a mechanical fusion machine and mixed for 5-15 min to obtain the raw material of Step 2-c; Step 3-c: The raw material obtained in Step 2-c is added to a tunnel furnace and heated and melted at 600℃-700℃; Step 4-c: The heated and melted product is cooled and graded to obtain the first microparticle.

9. A method for preparing hot-melt coating fillers according to any one of claims 1-8, characterized in that, The method includes the following steps: Step 1: preparing the first microparticle; Step 2: preparing the modified fiber material; Step 3: thoroughly mixing the first microparticle, Sn-Bi binary alloy powder, modified inorganic fiber material, calcium silicate, calcium carbonate and metakaolin to obtain the hot melt coating filler.

10. The use of the hot melt coating filler according to any one of claims 1-8 in a hot melt coating composition.